Obesity, Diabetes, and Metabolic Syndrome - Ghada Welwel (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2020)
In the contemporary society, there are various health factors that affect people, both the elderly and the young population based on their environment and the interconnected risk factors. Based on that, it is necessary to understand and comprehend that metabolic syndrome also known as (Mets) involves a combination of risk factors for glucose intolerance, insulin resistance, obesity, dyslipidemia, as well as hypertension [1].